Research Data Management at a Medical Facility in Uganda: Practices, Awareness, Challenges, and Recommendation - Edward Mukiibi; Joyce Bukirwa (Journal of eScience Librarianship)
The paper explored research data management practices at a medical research facility in Uganda. It focused on the researchers' perception about research data practices, awareness, and challenges. Mixed methods were applied in which thirty (30) respondents out of a population of sixty (60) research community members. The research community was comprised of both research teams and research support members. Whereas the research team respondents were selected randomly and subjected to the questionnaire, the four key informants were purposively selected from the research support members and subjected to the interview. The findings showed variations in perception, management, and understanding of research data practices. Identified challenges were inadequate legal framework, lack of institutionalised storage facilities, and limited competencies in writing Data Management Plans. The recommendations were: the formation of a unit for the development of research data management policy, support services, and the introduction of formal research data management skills training to equip the research community at the facility.